Edwards' personality preference schedule as correlated with the pre-clinical laboratory performance of UPCD batch '94 - Go, Serathina S.
This study was undertaken to learn if the personality inventories being given by the UP Manila's Guidance and Counselling Office can foe used as an additional screening criteria for the applicants to the dental proper program. The results of the psychological test, the Edwards' Personality Preference Schedule (EPF'S), were correlated to the pre-c1inical laboratory performance of the UPCD class '94,: "The findings suggest that there is no correlation between the personality profile and the students' laboratory performance. These profile's would not be a meaningful addition to the selection criteria fpr the proper program applicants